Regulation of intestinal dendritic cell migration and activation by plasmacytoid dendritic cells, TNF-alpha and type 1 IFNs after feeding a TLR7/8 ligand. - Yrlid, U; Milling, S; Miller, J; Cartland, S; Jenkins, C; Macpherson, G (2006)
Dendritic cells (DCs) migrating via lymph are the primary influence regulating naive T cell differentiation, be it active immunity or tolerance. How DCs achieve this regulation in vivo is poorly understood. Intestinal DCs are in direct contact with harmless or pathogenic luminal contents, but may also be influenced by signals from epithelial cells, macrophages, or other resident or immigrant cells. To understand the role of TLR7 and TLR8 in regulating intestinal DC function, we fed a TLR7/8 ligand (resiquimod (R-848)) to rats and mice and examined DC in pseudoafferent lymph (rat) and mesenteric lymph nodes (MLNs). Oral R-848 induced a 20- to 30-fold increase in DC output from the intestine within 10 h due to a virtually total release of lamina propria DCs. This resulted in an accumulation of DCs in the MLNs that in mice was completely TNF-alpha dependent. Surprisingly, intestinal lymph DCs (iL-DCs) released by R-848 did not up-regulate CD86, but did up-regulate CD25. In contrast, MLN-DCs from R-848-stimulated rats and mice expressed high levels of CD86. This DC activation in MLNs was dependent on type 1 IFNs. The major source of these rapidly released cytokines is plasmacytoid DCs (pDCs) and not classical DCs, because depletion of pDCs significantly reduces the R-848-stimulated increase in serum cytokine levels as well as the accumulation and activation of DCs in MLNs. These experiments show that TLR-mediated regulation of iL-DC functions in vivo is complex and does not depend only on direct iL-DC stimulation, but can be regulated by pDCs.